A study on continuous dependence of layered composite materials in binary mixtures on basic data - Yuanfei Li (Electronic Research Archive)
This paper investigates the continuous dependence of solutions to layered composite materials in binary mixtures on perturbation parameters defined in a semi-infinite cylinder. Due to the fact that the base of the cylinder is easily disturbed by compression, this causes disturbances to the data at the entrance. By introducing auxiliary functions related to the solution of the equations, this article analyzes the impact of these disturbances on the solutions of the binary heat conduction equations and obtains the continuous dependence of the solutions on the base.